Sexual Dimorphism in Balance and Coordination in p75NTRexonIII Knock-Out Mice - Abbasian, Mahdi; Langlois, Annick; Gibon, Julien (Frontiers in Behavioral Neuroscience, 2022)
The p75 neurotrophin receptor (p75NTR) is implicated in various biological functions during development and adulthood. Several animal models have been developed to identify the roles of p75NTR in vivo and in vitro. P75NTRExonIII knock-out mice are widely used to study the neurotrophin receptor and its signaling pathways. Similar to other models of p75NTR knock-out (p75NTRExon IV KO) or conditional knock-out (p75NTRfl/fl) mice, p75NTRExonIII knock-out mice present severe abnormalities in walking, gait, balance and strength. The present study identifies a sexual dimorphism in the p75NTRExonIII knock-out strain regarding balance and coordination. Using Kondziela’s inverted grid test, we observed that p75NTRExonIII knock-out males performed poorly at the task, whereas p75NTRExonIII knock-out females did not exhibit any defects. We also observed that female p75NTRExonIII knock-out mice performed significantly better than male p75NTRExonIII knock-out mice at the beam balance test. There were no differences in strength, skin innervation, or the number of ulcers on the toes between p75NTRExonIII knock-out males and females. The literature regarding the role of p75NTR in behavior is controversial; our results suggest that studies investigating the role of p75NTR in vivo using p75NTR knock-out mice should systematically report data from males and females.